On chrematonyms in reports by Melchior Wańkowicz from the Anoda i katoda collection - Guz, Marzena (Papers in Linguistics, 2020)
The article deals with chrematonyms in reports by Melchior Wańkowicz from the Anoda i katoda collection. The aim of the study is to present the diversity of this onymic category. The excerpted chrematonyms were assigned to five categories: names of cultural enterprises, names of institutions, names of companies, names of vehicles and names of products. Numerous subcategories were identified within each category, e.g. the names of cultural enterprises in Wańkowicz’s texts include titles of books, periodicals, articles in periodicals and titles of Wańkowicz’s feuilletons. Furthermore, the names of institutions include names of cultural institutions and financial institutions. The names of organisations and associations include: agricultural, military, aid organisations and others. Some attention was also devoted to a transition category between toponymy and chrematonymy, i.e. names of buildings and names of orders – phalaronyms. The set of cultural enterprises is the largest, with book titles dominating. Moreover, the aim of the study is also to demonstrate the function of chrematonyms in the texts under analysis. The chrematonyms in the Anoda i katoda collection typically perform three basic functions: the function of spatial location, the sociological function and the informational function.